ANALISIS SEBARAN TEMPERATUR DAN SALINITAS AIR LIMBAH PLTU-PLTGU BERDASARKAN SISTEM PEMETAAAN SPASIAL (STUDI KASUS : PLTU-PLTGU TAMBAK LOROK SEMARANG) - Haryono Setiyo Huboyo; Badrus Zaman (Universitas Diponegoro, 2007)
Heat wastewater emitted by power plant near seashore will be dispersed to bulk seawater by stream. The main effects generated by this elevated streams is deteriorating of benthic and aquatic life productivity. Further impact is subjected to depleting dissolved oxygen and seawater salinity content. By means of spatial mapping, the pattern of temperature distribution would be revealed and its impact could be predicted by then. Measurements of 14 purposive sampling spots were conducted in the early morning, noon and afternoon within Tambak Lorok Port pond. Control measurements also were taken in the East side and West side of the pond. Temperature distribution observed from the early morning through the afternoon exhibited the same pattern with dissolved oxygen distribution as well as stream pattern. Turbidity distribution accumulated in the East side, mixed with domestic waste stream carrying large amount suspended solids. Salinity distribution showed a little bit different pattern with temperature distribution considering that salinity pattern was affected by incoming streams from bulk seawater in the Northwest and Northeast of the pond.